CASE REPORTOchronotic spondylosis of 5 years old boy – a case report - Rutkowska-Sak, Lidia; Słowińska, Iwona; Kołodziejczyk, Beata (Reumatologia/Rheumatology, 2006)
Alkaptonuria is a rare disorder caused by congenital homogentisate oxidaze deficiency of recessive inheritance. Homogentisate polymers are accumulated and manifested with urine darkening and ochronosis. A 12 years case history of a boy aged 17 with intervertebral disc calcification intractu ochronosis is presented. The clinical picture, diagnostic and therapeutic possibilities are described.